The Effectiveness of Central Bank Intervention in the EMS: The Post 1993 Experience - Peter Brandner; Harald Grech; Helmut Stix (Oesterreichische Nationalbank (OeNB), 2001)
We analyze the effectiveness of intervention in the European Monetary System by using daily data on the DEM-intervention activity of six European central banks, covering the period from August 1993 to April 1998. To test for the influence of intervention we apply EGARCH models. To allow for regime specific intervention effects we also estimate Markov Switching autoregressive conditional heteroscedasticity models. The results from the EGARCH models show that interventions influenced the conditional mean in only one case. Both volatility increasing and decreasing effects are found for the conditional variance. In the MS-ARCH model more effects on the mean are found. If significant, intervention tends to affect the level of the six ERM I exchange rates only in periods of low and medium volatility. For the conditional variance more volatility decreasing than increasing effects are found. Overall, given our approaches (EGARCH and MS-ARCH), the results show that even in the same institutional framework, intervention does not seem to affect the means and variances in a consistent and predictable manner.
Keywords: E58; F31; F33; 330; Foreign Exchange Intervention; European Monetary System; EGARCH; Markov Switching ARCH